PENGARUH DEWAN DIREKSI PEREMPUAN TERHADAP MANAJEMEN LABA YANG DIMODERASI OLEH PERTUMBUHAN PENJUALAN: THE INFLUENCE OF A FEMALE BOARD OF DIRECTORS ON EARNING MANAGEMENT WHICH IS MODERATED BY SALES GROWTH - Andriany, Venny; Karina, Ria; Mardianto, Mardianto (Universitas Riau, 2023)
The purpose of this research is to find out whether female board of directors infleunce on earning management, also to research female board directors influence on earning management moderated by sales growth. The dependent variable in the research is earning management, the independent variable is the female board of directors, the moderating variable is sales growth and the control variable is female representation, company size, board size, and return on asset. The study used a data sample of 480 companies. The purposive sampling of method used in selecting sample is Indonesia Stock Exchange company, researches and the data using panel regression with a combination method of time series and cross-sectional data. Data is processed usig EViews version 12. The result of the study explain that female board of directors have no significant effecct on the earning managements and female board directors has significant effect on earning management through sales growth